Modernization of urban space with greenery = Modernizacja przestrzeni miejskiej zielenią - Sobolewski, Andrzej; Czajka, Roman (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Modernization of urban space with greenery is part of a process of revitalization and restoration of building, which today are an important part of the design and realizations activities in the world. Adaptation of urban space to modern needs, often associated with the change of the original function is necessary to improve the quality of this space: utility, technical and aesthetic.
Keywords: przestrzeń miejska; zieleń w mieście; modernizacja; rewitalizacja; urban space; greenery; modernization; revitalization